2017
DOI: 10.1002/jcb.25814
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Inhibited Human Mesenchymal Stem Cells Angiogenic Response by Over‐Activity of the Autophagic Pathway

Abstract: The current study aimed to address the impact of serum from type 2 diabetes patients on the angiogenic properties of human bone marrow mesenchymal stem cells and its relationship to autophagy signaling. Human primary stem cells were enriched and incubated with serum from diabetic and normal subjects for 7 days. Compared to data from the control group, diabetic serum was found to induce a higher cellular death rate (P < 0.001) and apoptotic changes (P < 0.01). We also showed that diabetic condition significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 48 publications
(59 reference statements)
2
48
1
2
Order By: Relevance
“…Another study of human mesenchymal stem cells indicated that, although diabetic sera induced autophagy at the early stage, it inhibited autophagy at a late stage. Inhibition of insulin on autophagy occurred through two mechanisms: by activating mTORC1 resulting in the inhibition of ULK1 and by activating protein kinase B, which inhibits FOXO3 [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Another study of human mesenchymal stem cells indicated that, although diabetic sera induced autophagy at the early stage, it inhibited autophagy at a late stage. Inhibition of insulin on autophagy occurred through two mechanisms: by activating mTORC1 resulting in the inhibition of ULK1 and by activating protein kinase B, which inhibits FOXO3 [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DM2 has adverse effects on MSCs function, inhibiting the angiogenic ability of MSCs through the downregulation of pro‐angiogenic factors. Furthermore, BM‐MSCs from diabetic patients show hampered paracrine secretion and an increased propensity to differentiate into adipocytes .…”
Section: Msc Donor‐related Variability Mattersmentioning
confidence: 99%
“…Consistent with our results, the transdifferentiation of diabetic CPCs to vascular cells such as ECs and pericytes and mature cardiomyocytes were inhibited after incubation with HGC which coincided with the down‐regulation of vWF, CD31, α‐SMA, NG 2 , and cTnT both in vitro and in vivo. Previously, Rezabakhsh and co‐workers found a decreased mesenchymal stem cell to EC differentiation under diabetic condition governed by an abnormal activity of autophagy marker P62 . In addition to reduced CPC differentiation into EC, no lipoprotein lipase activity was scored in CPCs subjected to medium with 30mM glucose.…”
Section: Discussionmentioning
confidence: 95%